Spirulina platensis Attenuates Cold Allodynia and Chemical Allodynia in Streptozotocin induced Diabetic Rats (KYAMC Journal, 2023)
Background: Diabetic neuropathic pain exerts strong as well as negative influence on both survival and quality of life of the patient. This pain is difficult to treat with conventional analgesics. Now a days, different medicinal herbs are highlighted due to their wide range of beneficial application with less side effects. In this regards Spirulina platensis is well known for its wide range of biological activities. Objective: To assess the effects of oral administration of Spirulina platensis on cold allodynia and chemical allodynia in diabetic neuropathic pain in Long Evans rats.Materials and Methods: This study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from March 2017 to February 2019. Twenty four (24) Long Evans rats, having 150 to 200 grams body weight (on the basis of treatments), the rats were divided into Group I (normal saline 5 ml/kg body weight) and Group II (Spirulina platensis 400 mg/kg body weight). All the supplementations were given once daily for consecutive 21 days orally and last doses were given one hour before the pain evaluation tests. Further on the basis of experiments, previously grouped rats were divided into subgroup ‘a’(cold tail immersion test), and ‘b’ (formalin test). Data were expressed as mean±SEM and were statistically analyzed by SPSS (Version 16) using independent sample ‘t’ test to compare mean value between two groups. (p 0.05 was considered as the level of significance).Results: Spirulina platensis showed significantly higher tail flick latency (p 0.001) in cold tail immersion test. S. platensis demonstrated significantly lowered jerking frequency (p 0.001,p 0.01,p 0.001, respectively); the duration of licking (p 0.001,p 0.05,p 0.001, respectively) and the duration of flexing (p 0.001, non-significant 0.01, respectively) in early, inter and late phases of formalin test in compared to those of control. Conclusion: S. platensis attenuates cold allodynia and chemical allodynia diabetic neuropathic pain in rat model.KYAMC Journal Vol. 13, No. 04, January 2023: 208-213